多元文化建构的重塑 ：郭宝崑90年代剧场的跨文化理念与实践 = Reconstructing multiculturalism : Kuo Pao Kun's transcultural theatre concept and practice from the 90's - 白艳琳 Pek, Yan Lin (Nanyang Technological University, 2021)
新加坡自独立以来标榜着“多元文化社会”，拥有丰富文化资产却一直实行 “单一化” 的制度。政府采取多元文化主义成为一种意识形态的依据，并合理化一切对于种族和社群的控制范围，使得族群之间对于文化认知显得肤浅。郭宝崑作为本地华语剧场的重要人物，成为推动新加坡文化的中介与推手，并以跨文化剧场的形式推动本地文化与艺术发展。本文将以郭宝崑90年代的戏剧作品为主要研究对象，探讨郭宝崑如何以跨文化剧场策略对新加坡文化开创新的理解模式，试图重塑官方所实行的的多元文化主义。Since its independence, Singapore has often prided itself as a “multicultural society” but has always seemingly implemented a homogeneous societal culture albeit its rich cultural resources. In such a multiracial, multireligious society, Singapore multicultural diversity is not seen as a valuable cultural resource but rather as a pluralism that need to be conformed and disciplined in order to establish a singular national identity, rationalised under the country multiculturalism ideology discourse. As such, races in Singapore are divided from each other with a shallow understanding of each other culture. As a playwright, theatre director, and social activist, Kao Pao Kun was a crucial pioneer of the Singapore Chinese Theatre. He played a major role in mediating and promoting Singapore’s arts and culture through the form of transcultural theatre. This paper aims to examine on Kuo Pao Kun’s idea of Singapore “open culture” by drawing on a collection of his plays set in the 90s, and his attempt on using transcultural theatre as a strategy to re-construct and reimagine multiculturalism in Singapore.